More on the perforation of concrete slabs by rigid projectiles. (April 2022) - Rosenberg, Z.; Vayig, Y.; Malka-Markovitz, A.; Kositski, R.
Highlights: We analyze the recent experimental data on concrete slabs perforated by ogive-nosed rigid projectiles. The analysis is based on our penetration/perforation models for concrete targets. The analysis includes the scaling issue in concrete penetration which was resolved by us recently. The agreement between our analytical predictions and the data is shown to be very good for the ballistic limit velocities, and for the residual velocities of the projectiles perforating these slabs. Abstract: We demonstrate the validity and usefulness of our recently-published model for the perforation of concrete slabs by rigid projectiles. The model also accounts for the scaling issue in concrete penetration/perforation, which presented a longstanding obstacle in modeling the concrete's response to projectile impact. Comparing predictions of the model with several sets of data on concrete slab perforation, show very good agreement as far as ballistic limits and residual velocities are concerned.